CROSS-SECTIONAL EPIDEMIOLOGICAL STUDIES ON MASTITIS IN CATTLE AND BUFFALOES OF TEHSIL BUREWALA, PAKISTAN - S. Hameed; M. Arshad; M. Ashraf; M. Avais; M. A. Shahid (Journal of Animal and Plant Sciences, 2012)
The present study was contemplated to find out the epidemiology of mastitis in lactating cattle and buffaloes in tehsil Burewala, Pakistan. For this purpose, a total of 673 animals (n=291 cattle, n=382 buffaloes) from 300 livestock farmers were tested using Surf Filed Mastitis Test (SFMT) for the presence of mastitis. A higher prevalence (24.60%) of clinical mastitis was found in buffaloes than cattle (18.21%). The prevalence of sub-clinical mastitis was 36.38% and 33.67% in buffaloes and cattle, respectively. Quarter based prevalence of clinical mastitis in buffaloes and cattle was 8.04% and 5.75%, respectively. Quarter based prevalence of sub-clinical mastitis was 16.04% in buffaloes and 14.47% in cattle. Risk factors of mastitis found were: age, lactation number, stage of pregnancy, stage of lactation, dry period length, hard milking, calf suckling, folded thumb milking technique, teat injury, backyard housing, bricks floor, uneven floor, poor drainage system and low frequency of dung removal.
Keywords: mastitis; prevalence; cattle; buffaloes; quarter; Surf Field Mastitis Test